2020
DOI: 10.1007/s12223-020-00816-2
|View full text |Cite
|
Sign up to set email alerts
|

RamA, a transcriptional regulator conferring florfenicol resistance in Leclercia adecarboxylata R25

Abstract: Due to the inappropriate use of florfenicol in agricultural practice, florfenicol resistance has become increasingly serious. In this work, we studied the novel florfenicol resistance mechanism of an animal-derived Leclercia adecarboxylata strain R25 with high-level florfenicol resistance. A random genomic DNA library was constructed to screen the novel florfenicol resistance gene. Gene cloning, gene knockout, and complementation combined with the minimum inhibitory concentration (MIC) detection were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…These two genes were also present of the genom of Leclercia sp. 29361 and also described to appear in this genus by other authors 81 . Lelliottia amnigena, previously classified as Enterobacter amnigena, itself…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…These two genes were also present of the genom of Leclercia sp. 29361 and also described to appear in this genus by other authors 81 . Lelliottia amnigena, previously classified as Enterobacter amnigena, itself…”
Section: Discussionsupporting
confidence: 56%
“…Sequence variants of marA have been described in Leclercia spp. 13 , while acrB and ermB have been mentioned related to this species 80,81 . In contrast, BacA, KpnH, msbA and oqxA has not been mentioned to appear within the genom of Leclercia spp.…”
Section: Discussionmentioning
confidence: 97%
“…One possible explanation is that the modification on florfenicol with COS impaired the drug-resistant machinery. Bacteria gain the resistance to florfenicol partially by the drug efflux pump system, leading to reduced drug concentration in the bacteria cells [ 28 ]. Our previous study showed that COS modification on streptomycin suppressed the MexX-MexY drug efflux pump system in P. aeruginosa [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus ATCC 29213 and Escherichia coli ATCC 25922 were used as quality control strains in antimicrobial susceptibility testing experiments. E. coli strain DH5α and pUCP24 plasmid were used as a recipient and vector in cloning experiments ( Cheng et al, 2020 ), respectively.…”
Section: Methodsmentioning
confidence: 99%